Dynamics of Erythroferrone Response to Erythropoietin in Rats - Xu, Peng; Wong, Raymond S. M.; Krzyzanski, Wojciech; Yan, Xiaoyu (Frontiers in Pharmacology, 2022)
Background: Erythroferrone (ERFE) is a hormone identified recently as a master regulator connecting iron homeostasis and erythropoiesis. Serum ERFE concentrations significantly increase in animals and humans with normal or impaired kidney function after receiving exogenous erythropoiesis-stimulating agents (ESAs), which suggests it might be a predictive factor for erythropoiesis. To evaluate whether ERFE is an early, sensitive biomarker for long-term erythropoietic effects of ESAs, we investigated the relationship between ERFE dynamics and time courses of major erythropoietic responses to ESA treatment. Methods: Healthy rats received single dose and multiple doses (thrice a week for 2 weeks) of recombinant human erythropoietin (rHuEPO) at three dose levels (100, 450, and 1350 IU/kg) intravenously. The rHuEPO and ERFE concentrations in plasma were determined at a series of time points after dosing. Erythropoietic effects including red blood cell count and hemoglobin concentrations were continuously monitored for 24 days (single dose) or 60 days (multiple doses). The expansion of erythroblasts in bone marrow was quantified by flow cytometry analysis. Results: ERFE significantly increased within a few hours and return to baseline at 24 h after rHuEPO treatment. The ERFE response was enhanced after repeated treatment, which was consistent with the observed expansion of erythroblasts in the bone marrow. In addition, the dynamics of ERFE showed double peaks at approximately 2 h and 10 h after rHuEPO stimulation, and the ERFE baseline displayed a significant circadian rhythm. There was a strong positive correlation between peak values of short-term ERFE responses and the long-term hemoglobin responses. Conclusions: The stimulated release of ERFE is a rapid process within 24 h. The second peak in the ERFE response to rHuEPO suggests the presence of a feedback mechanism counterregulating the ESA stimulation. The early increase of ERFE at 2 h appears to be a predictor of the hemoglobin response at 14 days after single dose of rHuEPO. Under multiple-dose regimen, the enhanced ERFE responses still correlate with the peak hemoglobin responses. The ERFE baseline also exhibits a circadian rhythm.